Learning context effects Study abroad, formal instruction and international immersion classrooms - Pérez Vidal, Carmen; López-Serrano, Sonia; Ament, Jennifer; Thomas-Wilhelm, Dakota J. (Language Science Press, 2018)
This book deals with the effects of three different learning contexts mainly on adult, but also on adolescent, learners' language acquisition. The three contexts brought together in the monograph include i) a conventional instructed second language acquisition (ISLA) environment, in which learners receive formal instruction in English as a Foreign Language (EFL); ii) a Study Abroad (SA) context, which learners experience during mobility programmes, when the target language is no longer a foreign but a second language learnt in a naturalistic context; iii) the immersion classroom, also known as an integrated content and language (ICL) setting, in which learners are taught content subjects through the medium of the target language-more often than not English, used as the Lingua Franca (ELF).